The [FeFe] hydrogenase of Nyctotherus ovalis has a chimeric origin - Boxma, Brigitte (BioMed Central, 2007)
BACKGROUND: The hydrogenosomes of the anaerobic ciliate Nyctotherus ovalis show how mitochondria can evolve into hydrogenosomes because they possess a mitochondrial genome and parts of an electron-transport chain on the one hand, and a hydrogenase on the other hand. The hydrogenase permits direct reoxidation of NADH because it consists of a [FeFe] hydrogenase module that is fused to two modules, which are homologous to the 24 kDa and the 51 kDa subunits of a mitochondrial complex I. RESULTS: The [FeFe] hydrogenase belongs to a clade of hydrogenases that are different from well-known eukaryotic hydrogenases. The 24 kDa and the 51 kDa modules are most closely related to homologous modules that function in bacterial [NiFe] hydrogenases. Paralogous, mitochondrial 24 kDa and 51 kDa modules function in the mitochondrial complex I in N. ovalis. The different hydrogenase modules have been fused to form a polyprotein that is targeted into the hydrogenosome. CONCLUSION: The hydrogenase and their associated modules have most likely been acquired by independent lateral gene transfer from different sources. This scenario for a concerted lateral gene transfer is in agreement with the evolution of the hydrogenosome from a genuine ciliate mitochondrion by evolutionary tinkering.